Advances in taxation. 27 - Hasseldine, John (Emerald Publishing Limited, 2020)
In the latest volume of Advances in Taxation, series editor John Hasseldine presents studies from expert contributors exploring topics such as: corporate tax planning, taxrelated accounting misstatements and uncertain tax positions, financial statement readability, the tax effects of a major pension scheme change, and nonprofessional investor and taxpayer judgments and perceptions. Reporting peerreviewed research contributions from North America and the U.K., this volume is essential reading for those looking to keep abreast of the most recent research, including empirical studies using a variety of research methods from different institutional settings and contexts.
Introduction / John Hasseldine -- Chapter 1. Do creditors influence corporate tax planning? Evidence from loan covenants / Kirsten Cook, Tao Ma, and Yijia (Eddie) Zhao -- Chapter 2. Tax-related accounting restatements and taxcontingency reporting / Paul N. Tanyi, J. Philipp Klaus, and Hughlene Burton -- Chapter 3. Annual report readability and share repurchases under a temporary tax holiday / Xin Zhao, Greg Filbeck, and Ashutosh Deshmukh -- Chapter 4. Tax planning activities and firm value: a dynamic panel analysis / Alan Kirkpatrick and Dragana Radicic -- Chapter 5. Taxation, pension schemes and stakeholder wealth / Emmanouil Platanakis and Charles Sutcliffe -- Chapter 6. The impact of countrybycountry reporting on nonprofessional investor / Stephanie Walton and Michael Killey -- Chapter 7. The effects of individual values on willingness to pay and fairness perceptions of use tax on internet purchases / Lixuan Zhang, Eric Smith, and Andrea Gouldman.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Taxation -- Periodicals; Business & Economics, Taxation -- General; Taxation